Factors That Influence UKMPPD Failure - A. Muh. Akbar Batara Putra A.M; Febie Irsandy Syahruddin; Darariani Iskandar (Sean Institute, 2024)
The Competency Test for Medical Professional Program Students (UKMPPD) is the final stage to assess student competence before getting a professional certificate . Failure to pass the UKMPPD is influenced by several factors . This research aiming to identify and analyze the factors that influence failure to pass the Medical Education Program Student Competence Examination (UKMPPD), with a focus on academic readiness , learning methods , and individual factors such as stress , motivation , and social support . The research method included a literature review of various previous studies discussing failure to pass medical competency exams . The analysis results show that academic readiness which includes understanding the material and practical skills is very important to achieve satisfactory exam results . In addition , learning methods that do not match the exam format as well as individual factors such as high stress levels and lack of social support also contribute significantly to failure to pass . This research suggests improving more active and realistic learning methods as well as providing adequate emotional support to reduce future failure rates .